2021
DOI: 10.1038/s41598-021-86831-w
|View full text |Cite
|
Sign up to set email alerts
|

Tumor innervation and clinical outcome in pancreatic cancer

Abstract: Pancreatic cancer is a highly aggressive malignancy characterized by poor survival, recurrence after surgery and resistance to therapy. Nerves infiltrate the microenvironment of pancreatic cancers and contribute to tumor progression, however the clinicopathological significance of tumor innervation is unclear. In this study, the presence of nerves and their cross-sectional size were quantified by immunohistochemistry for the neuronal markers S-100, PGP9.5 and GAP-43 in a series of 99 pancreatic cancer cases ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 39 publications
2
41
0
Order By: Relevance
“…It has been suggested that the innervation of cancer tissue is a new hallmark of cancer [ 114 ]. In support of this, it has been demonstrated that increased nerve size and density represents a negative prognostic marker of cancer disease [ 7 , 115 , 116 , 117 , 118 ].…”
Section: Drugs Reducing Density or Activity Of Nerves Innervating Cancer Tissuementioning
confidence: 90%
See 1 more Smart Citation
“…It has been suggested that the innervation of cancer tissue is a new hallmark of cancer [ 114 ]. In support of this, it has been demonstrated that increased nerve size and density represents a negative prognostic marker of cancer disease [ 7 , 115 , 116 , 117 , 118 ].…”
Section: Drugs Reducing Density or Activity Of Nerves Innervating Cancer Tissuementioning
confidence: 90%
“…Neurotransmitters released from nerves innervating cancer exert complex effects on cancer progression and the development of metastases [ 122 ]. These effects depend on the type of nerves [ 105 ] and their density in cancer tissue [ 7 , 115 , 116 , 117 , 118 ]. For example, norepinephrine released from sympathetic nerves plays an important role in the initial phases of prostate cancer development, while acetylcholine released from parasympathetic nerves potentiates the progression of prostate cancer and development of metastases [ 7 ].…”
Section: Drugs Reducing Density or Activity Of Nerves Innervating Cancer Tissuementioning
confidence: 99%
“…It also showed a significant association between the presence of nerves and poor survival for patients < 50 years of age. However, the small sample size of 11 patients did not allow for definitive conclusions 54 .…”
Section: Accepted Articlementioning
confidence: 93%
“…Another factor to consider when evaluating nerves in a tumor is the variability in morphological appearance of the nerve segments. Some studies showed that nerves within tumors are larger than nerves in normal tissues 40,53,54 . Another study showed that nerve size is comparable between chronic pancreatitis and pancreatic cancer, and that nerves are reduced in size when tumor stroma is desmoplastic 44 .…”
Section: Nerve Densitymentioning
confidence: 99%
See 1 more Smart Citation